PHYSICAL EDUCATION, THE PHYSICAL EDUCATOR AND THE MEDIA: AN INITIAL DISCUSSION (Fiep Bulletin - online, 2012)
The discussion on media and individuals in society is a context constantly debated in academic circles, however, necessary to make an initial discussion on the influence of the media with the academic and physical educators. The objective of this paper is to bring initial thoughts based on discussions in the discipline bringing sociology and physical education elements, although introductory screen to the debate. The methodology used was based on discussions, readings and guidance to, which ended in a thematic workshop at the University of Pará UEPA-campus XII, Santarém, on Physical Education and media. That way, there was the need for this debate in order to guide students to this dialectic process, present in media and academic life of the future primarily as a physical education teacher.
Keywords: Media; Physical Education; Physical Educator